2004
DOI: 10.1161/01.cir.0000136023.70841.0f
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Coenzyme A:Cholesterol Acyltransferase Inhibition Ameliorates Proteinuria, Hyperlipidemia, Lecithin-Cholesterol Acyltransferase, SRB-1, and Low-Denisty Lipoprotein Receptor Deficiencies in Nephrotic Syndrome

Abstract: Background-Nephrotic syndrome (NS) is associated with hyperlipidemia, altered lipid regulatory enzymes and receptors, and increased risk of progressive renal and cardiovascular diseases. Acyl-coenzyme A:cholesterol acyltransferase (ACAT) catalyzes intracellular esterification of cholesterol and plays an important role in production of apolipoprotein B-containing lipoproteins, regulation of cholesterol-responsive proteins, and formation of foam cells. Because hepatic ACAT-2 is markedly upregulated in NS, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 52 publications
5
35
0
Order By: Relevance
“…Previously, we had shown in animal models of spontaneous and puromycin aminonucleoside-induced nephrotic syndrome that hepatic LDLR gene expression level is normal; these new findings help explain why the receptor nevertheless is depleted in nephrotic syndrome. [5][6][7][8] By mediating degradation and limiting recycling of LDLR, upregulation of PCSK9 must play a major role in the pathogenesis of hypercholesterolemia and the associated risk of cardiovascular disease, as we have shown in both humans and animals with nephrotic syndrome. Several studies have demonstrated significant direct correlations between plasma PCSK9 and LDL cholesterol levels in the general population.…”
Section: Association Of Pcsk9 With Hypercholesterolemiamentioning
confidence: 82%
See 3 more Smart Citations
“…Previously, we had shown in animal models of spontaneous and puromycin aminonucleoside-induced nephrotic syndrome that hepatic LDLR gene expression level is normal; these new findings help explain why the receptor nevertheless is depleted in nephrotic syndrome. [5][6][7][8] By mediating degradation and limiting recycling of LDLR, upregulation of PCSK9 must play a major role in the pathogenesis of hypercholesterolemia and the associated risk of cardiovascular disease, as we have shown in both humans and animals with nephrotic syndrome. Several studies have demonstrated significant direct correlations between plasma PCSK9 and LDL cholesterol levels in the general population.…”
Section: Association Of Pcsk9 With Hypercholesterolemiamentioning
confidence: 82%
“…7,24 The potential role of upregulation of ACAT-2 is evidenced by the dramatic amelioration of hypercholesterolemia and marked reduction in plasma LDL cholesterol level with administration of ACAT inhibitor in animals with nephrotic syndrome. 7 In addition, by lowering the uptake of LDL and its cholesterol cargo from the circulation, depletion of hepatic LDLR in nephrotic liver contributes to the reduction in hepatocyte cholesterol, which can increase PCSK9 expression by activation of SREBP-2. Thus, upregulation of PCSK9 and depletion of LDLR participate in a vicious circuit in which each begets and intensifies the other.…”
Section: Association Of Pcsk9 With Hypercholesterolemiamentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Recently in Nature Medicine, Clement et al 4 published a series of experiments that showed that elevation of circulating angiopoietin-like 4 (Angptl4 in rats; ANGPTL4 in humans) appears to be the missing link that ties hypertriglyceridemia to albuminuria in nephrotic syndrome. Nephrotic hyperlipidemia is due largely to the acquired deficiencies of lipoprotein lipase (LPL), [5][6][7] hepatic lipase, 8 the VLDL receptor, 5,9 the LDL receptor, [10][11][12] lecithin-cholesterol acyltransferase (LCAT), 13 and the HDL docking receptor (SRB1; encoded by SCARB1) 14,15 ; upregulation of cholesterylester transfer protein (CETP), 16,17 hepatic acyl coenzyme A cholesterol acyltransferase (ACAT, encoded by ACAT1), 18,19 diglycerol acyltransferase, 20 and lipoprotein(a) 21 ; and altered composition of plasma lipoproteins interfering with their receptor binding and clearance. 22 Triglyceride-rich lipoproteins (VLDL and chylomicrons) deliver fatty acid to various tissues, including myocytes for energy production and adipocytes for energy storage.…”
mentioning
confidence: 99%